Deepening and broadening the field: introduction to Research Handbook on Nonprofit Governance - Donnelly Cox, Gemma (Edward Elgar, 2021)
Governance has in many respects become the new management. Just as management succeeded administration from the 1960s onwards (Grey, 1999), so governance has replaced management as the label for steering practices and the distribution of authority in organizations, nation states, politics and various other subfields of society. In this introductory chapter, we will weave the contributions to this Handbook together with prior research into the governance ‘story’ of the 2020s, and thereby discuss the ways in which the Research Handbook on Nonprofit Governance covers and advances the field. We structure this chapter as follows. First, we review governance definitions and the development of the nonprofit governance concept. Then we map the field of non-profit governance through a focus on organizing contexts, environmental contexts and constituencies, and we consider some of the governance practices that emerge within them. Next, we examine the governance theory–practice nexus by sketching out the theoretical perspectives considered by the Handbook’s contributors. We conclude by indicating some of the lacunae that remain.
Research Handbook on Nonprofit Govenance
PUBLISHED
Cheltenham, United Kingdom and Northampton, Mass, USA
Keywords: Identities in Transformation; accountability and transparency; nonprofit governance codes; nonprofit governance definitions; nonprofit governance theory; nonprofit regimes; stakeholder influences